QSVI: Interdisciplinary Optimization Clinic Decreases Infection in Neuromuscular/Syndromic Scoliosis Patients - McIntosh, Amy; Smith, Matthew; Wilder, Kerry (Journal of the Pediatric Orthopaedic Society of North America, 2020)
Background: Spinal surgery in pediatric neuromuscular and syndromic (NMS) patients is complicated and associated with numerous perioperative adverse events, unplanned reoperations, and suboptimal outcomes. SSIs are hospital acquired infections (HAIs), and they contribute to substantial morbidity in this patient population. This quality initiative (QI) focused on the development of a patient centered interdisciplinary medical optimization clinic and implementation of a standardized care pathway for NMS spinal fusion patients. Methods: In late 2017, an interdisciplinary committee was formed with the purpose of creating a patient centered medical optimization clinic for surgical patients with neuromuscular and syndromic scoliosis. It was labeled, the Neuromuscular and Syndromic Spine Pathway (NSP) Clinic. All NSP patients had standardized pre-surgical assessment. The aims of the initiative were to 1) measure compliance to the implemented NSP clinical pathway by creating standardized order sets in the electronic medical record (EMR) (EPIC), 2) create a free patient mobile app to address the following: a. coordination of necessary pre-operative appointments/consults, and b. pre and post- operative education (video links, hospital tour, provider contact information, and 3) reduced HAI SSI in NMS spinal fusion patients with a target goal of zero. The committee retrospectively reviewed the prospectively collected data for all NMS spine SSIs from 1/1/2018 to 12/31/2019. All infections were reviewed using Root Cause Analysis (RCA) methodology. Infection rates were calculated using rolling 6 month averages. Intervention: A “pilot” group of patients were evaluated and medically optimized through the NSP clinic. The NSP patient’s SSI risk was calculated using the Risk Severity Scale (RSS) pre-operatively16. This was compared to the actual HAI SSI rate to determine if the SSI risk could be positively modified through pre-operative medical optimization. Results: From 1/2018 -12/2019, 160 NMS patients underwent spinal fusion. 29 (18%) of those were medically optimized in the NSP clinic. There were 13 M and 16 F patients. The average age was 12.8 years, pre-op cobb angle was 85.4°, the pre-operative kyphosis was 76.1°, and the average pre-operative BMI was 17.4. The average pre-operative SSI RSS was calculated to be 19.69%. 0/29 (0%) NSP patients developed a HAI SSI. (p = 0.015) Whereas, 9/131 (6.9%) NMS scoliosis fusion patients that were “not cleared” (NC) through the NSP clinic developed a HAI SSI. By utilizing RCA methodology, a common trend was observed. In 2018, 9/69 (13.0%) patients that were NC through the NSP clinic developed a HAI SSI. 7/9 (77.7%) of those infections were due to S. aureus species. This drove the implementation of the second initiative. Second Intervention: The goal of this initiative was to create and implement a S. aureus screening and decolonization program for NMS scoliosis patients undergoing spinal fusion surgery at our institution. The pre- surgical screening was accomplished by culture of the anterior nares, tracheostomy tube, and/or gastrostomy tube sites. A positive culture for either methicillin-sensitive S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA) was followed by decolonization with nasal mupirocin (2x/day) and a daily CHG bath for five days prior to the surgical date. The protocol utilized rapid (Plan-Do-Check-Act) cycles with a goal to reduce the HAI SSI rate due to S. aureus species in NMS spinal fusion patients within 1 year. Results: 68 NMS spinal fusion patients were screened for S. aureus colonization in 2019. Of the 68 patients screened, 36.8% (25/68) tested positive for S. aureus colonization. The prevalence of MSSA was 30.9% (21/68), while the prevalence of MRSA was 5.88% (4/68). The majority (68%) of organisms were culture positive in the anterior nares, 16 % from the gastrostomy tube, and 16% in both nares and gastrostomy tube. The HAI SSI rates for spinal fusion NMS patients decreased to 0/72 (0%) in 2019 (p= 0.003). Conclusion: Patient centered interdisciplinary pre-operative medical optimization modified the SSI risk in this “pilot” group of NMS scoliosis patients. The NSP clinic cohort had a 20% predicted risk of developing a HAI SSI, and actual rate was 0%. In contrast, 6.9% of the NMS scoliosis fusion patients that were NC through the NSP clinic developed an HAI SSI. 77.7% of those infections were due to S. aureus species. This drove the S. aureus screening and decolonization initiative which decreased the HAI SSI rate to zero within one year’s time. As a result of these QIs, ALL NMS spinal fusion patients at our institution are screened for S. aureus colonization, and medically optimized through the NSP clinic.